The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Bronzoni, Roberta V. M.; Madrid, Maria C. F. S.; Duarte, Danilo V. B.; Pellegrini, Vanessa O. A. [UNESP]; Pacca, Carolina C. [UNESP]; Carmo, Ana C. V. [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP]; Santacruz-Perez, Carolina; Barbosa, Joao A. R. G.; Lutz, Carol S.; Rahal, Paula [UNESP]; et al. (Springer Wien, 2011)
The flavivirus NS5 protein is one of the most important proteins of the replication complex, and cellular proteins can interact with it. This study shows for the first time that the yellow fever virus (YFV) NS5 protein is able to interact with U1A, a protein involved in splicing and polyadenylation. We confirmed this interaction by GST-pulldown assay and by co-immunoprecipitation in YFV-infected cells. A region between amino acids 368 and 448 was identified as the site of interaction of the NS5 protein with U1A. This region was conserved among some flaviviruses of medical importance. The implications of this interaction for flavivirus replication are discussed.